Analisis Work Life Balance dalam Meningkatkan Kinerja Pegawai pada Kantor Kelurahan Sepatan KabupatenTangerang - Maswarni, Maswarni; Nofiar, Nofiar; Rachmawati, Rachmawati (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research is to analyze Work Life Balance in improving employee performance at the Sepatan Tangerang Village Office. The research is carried out by quantitative methods, namely in-depth study of social problems based on the creation of a complete holistic picture formed by words. Analysis techniques include: data collection, data reduction, data presentation and conclusion Checking the validity of the data by triangulation and member checks. The results of the study obtained that the level of service quality of employees in serving the community is quite good and does not get obstacles where the community is served quickly and well because work-life balance has been achieved, namely a person's ability to balance between work demands and personal and family needs, namely Work-Life Balance with an individual's ability to fulfill work and employee family commitments and non-work responsibilities others that are going well.